ANALYSIS OF POTENTIAL DRUGS INTERACTION ON ANTIHYPERTENSION DRUGS PRESCRIPTION IN COMMUNITY HEALTH CENTER OF SUKMAJAYA DISTRICT IN PERIOD OF JUNE-NOVEMBER 2015 - Puspitasari, Atika Wahyu; Azizahwati, Azizahwati; Hidayat, Ayu Rahmawati (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Hypertension is a common disease around the world. Depending on the severity or the presence of other diseases, whether related or unrelated, additional drug therapy may be required to optimize treatment and to reduce the side effects of drugs. The use of drugs in large amounts may increase the risk of drug interactions. The purpose of this research was to evaluate the characteristics of hypertension patients, prescriptions, and potential drug interactions in hypertensive patients in the Sukmajaya Community Health Center from June to November 2015. Methods: This research used a descriptive analytic method and the data were retrospectively obtained. Results: The results were based on the analysis of 350 prescriptions of female (67.43%) and male (32.57%) patients, with the highest prevalence of hypertension occurring at the age of â‰¥55 years. Potential drug interactions were analyzed using Micromedex. The most frequent potential interaction resulted from the combined use of captopril and non-steroidal anti-inflammatory drugs. The most frequent mechanism of drug interaction was pharmacokinetics (51.06%). The chi-square test results showed a significant relationship between the number of prescribed drugs and potential interactions at a probability value of 0.0001 and an odds ratio of 5.940 (15.588-2.263). Conclusions: With respect to interaction mechanism, pharmacokinetic (51.06%) was the most frequent and 61.70% of potential cases involved a moderate interaction risk.